Personality traits and complex problem solving: Personality disorders and their effects on complex problem-solving ability - Kipman, Ulrike; Bartholdy, Stephan; Weiss, Marie; Aichhorn, Wolfgang; Schiepek, Günter (Frontiers in Psychology, 2022)
Complex Problem Solving (CPS) can be interpreted as the number of psychological mechanisms that allow us to reach our targets in difficult situations, that can be classified as complex, dynamic, nontransparent, interconnected and multilayered as well as polytelic. Previous results demonstrated associations between the personality dimensions neuroticism, conscientiousness and extraversion and problem solving performance. However, there are no studies dealing with personality disorders in connection with CPS skills. Therefore, the current study examines a clinical sample consisting of people with personality and/or depressive disorders. As we have data for all potential personality disorders and also data from each patient regarding to a potential depression, we meet the whole range from healthy to impaired for each personality disorder and for depression. We make use of a unique operationalization: CPS was surveyed in a simulation game, making use of the microworld approach. This study was designed to investigate the hypothesis that personality traits are related to CPS performance. Results show that schizotypal, histrionic, dependent and depressive persons are less likely to successfully solve problems, while persons having the additional behavioral characteristics resilience, action orientation and motivation for creation are more likely to successfully solve complex problems.